Factors determining the effectiveness of celebrity endorsed advertisements: the case of Jakel Kuala Lumpur / Nazatul Atikah Hashim and Nor Diana Zainal - Hashim, Nazatul Atikah; Zainal, Nor Diana (Faculty of Business and Management, 2016)
The main purpose of this study is to study the factors determining the effectiveness of celebrity endorsed advertisements: The case of Jakel Kuala Lumpur. In theory parts are described four factors which are perceived expertise, trustworthiness, attractiveness and credibility. A descriptive research design was adopted for this study. The data was collected from 125 respondents that are customers of Jakel Kuala Lumpur. In addition, from the SPSS analysis, it indicates that there is a relationship between perceived expertise and effectiveness of celebrity endorsement in advertisement. However, the finding also shows that there are no relationship between trustworthiness, attractiveness and credibility with effectiveness of celebrity endorsement in advertisement. Next, the findings also stated that perceived expertise is the most influencing factor that can influence the effectiveness of celebrity endorsement. All the findings of this study can be used and improvised in the future in order to get the better results.